Assessing Financial Determinants of Market Price in Nepalese Commercial Banks (Southwestern Research Journal, 2024)
This study is designed to identify the effect of interest income, interest expenses, net profit, earnings per share (EPS), retained earnings, dividend payout and book value per share on market price per share (MPS). Out of twenty-six commercial banks, five commercial banks including one governmental bank were selected on judgmental basis. Financial tool and statistical tools are considered to find the result showing the relationship between the dependent variable that is MPS and independent variables that are interest income, interest expenses, net profit, EPS, retained earnings, dividend payout and book value per share. The correlation results shows that MPS have positive relationship among net profit, EPS, dividend payout and book value per share however, MPS have negative relationship with interest income, interest expenses and retained earnings. Among the positive relationship MPS have strong positive relationship with dividend payout. Furthermore, the regression analysis showed shown that only two independent variables have significant impact on MPS and other variables have insignificant impact on MPS. EPS and dividend payout has significant positive relationship with MPS. The EPS and dividend payout has positive coefficient with the MPS. This study shows that the investor gives more priority to EPS and dividend payout of the bank before investing in the shares of the commercial bank. And it can also be inferred that if the company is able to make more profit and declare dividend payout; the market price of the company will be higher.